Global Assessment of Qibla Orientation in Mosques Using Satellite Imagery: A Geospatial and Islamic Astronomy Approach - Iin Lailatur Rohmah; Siti Tatmainul Qulub (Astroislamica: Journal of Islamic Astronomy, 2026)
This study analyzes the accuracy of mosque building orientations relative to the actual Qibla direction in various regions of the world using Google Earth technology through geospatial and Islamic astronomy approaches. Using quantitative-descriptive methods, this study involved four representative mosques from the four cardinal directions to the Kaaba: the Blue Mosque in Turkey, the Jama Mosque in India, the Istiqlal Mosque in Kenya, and the Al-Azhar Mosque in Egypt. Data were collected through geographic coordinates, building orientation measurements, theoretical Qibla direction calculations using the great circle bearing formula, and deviation analysis based on satellite imagery. The results show that the Qibla direction deviation varies between 0.1° and 4.7°, with an average of less than 3°, indicating a very high level of accuracy. Mosques in regions closer to Mecca, such as Turkey and Egypt, show minimal deviations, while mosques in India and Kenya have slightly larger deviations due to the influence of traditional methods and local architectural factors. The research conclusion confirms that the integration of geospatial and astronomical methods is effective in validating the direction of the Qibla globally and has the potential to support the development of digital mapping systems and the calibration of the Qibla direction in historic mosques in various countries.